LEGITIMASI HUKUM ADAT BALI DALAM KARYA SASTRA KULTURAL - I Kadek Adhi Dwipayana; Ida Bagus Gede Bawa Adnyana (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
Legitimacy of Balinese Customary Lawin Cultural Literature Works. This article talks about the legitimacy of Balinese customary law and the reinterpretation of the authors of Balinese customary law in cultural literary works. The source of research data comes from the collection of "Bunga Jepun" short stories by Fajar Arcana, "Mandi Api" by Aryantha Soethama, Novel "Tarian Bumi" by Oka Rusmini, and "Incest" by Wayan Artika. The research data was collected by the library study method and then analyzed based on a qualitative descriptive approach which has several mechanisms, namely reduction, presentation of data, and drawing conclusions. The results of the study indicate that the legality of Balinese customary law in question in cultural literature is about the customary law of marriage, the law of inheritance, the law of neglect (exclusion), and the ritual law of malik sumpah. These customary laws become a polemic and are discussed in literary works because they are unable to provide justice for the people and tend to be discriminatory. These customary laws are polemic and are discussed in literary works because they are unable to provide justice among indigenous people